A Performance Measurement Model for Shariah Banks Based on Falah - Mursyid, Mursyid; Yanti, Dharma; Lamtana, Lamtana; Shufiah, Wardatush (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2024)
It is the financial ratio, risk, or capital ownership approach that dominates the performance of conventional and sharia banking. In order to evaluate the performance of sharia banking, a measurement model that is consistent with the principles of sharia economics is necessary, as the operational basis of sharia banks and conventional banks is significantly different. This model must not only evaluate the financial performance but also the normative side. All Muslim activities and behaviors on Earth are ultimately directed toward falah, as is widely recognized. As a result, the objective of this investigation is to develop a falah-based sharia bank performance measurement model and to evaluate the performance of ten sharia commercial banks in Indonesia. The Simple Additive Weighting Method is employed to accomplish weighting and aggregation in the falah approach to performance compilation, while the two-phase multiattribute decision-making approach is employed to determine ranking. The development of the performance measurement model of the Maqashid Syariah Index is designated as Falah in this study. According to the Falah approach, the performance evaluation of sharia institutions reveals that Bank TB Bukopin Syariah and BTPN Syariah exhibit flawless performance. At the same time, Bank Aladin Syariah, Bank Panin Dubai Syariah, Bank Aceh Syariah, Bank Muamalat, and BJB Syariah demonstrated exceptional performance. In addition, Bank Mega Syariah demonstrated satisfactory performance.